2015
DOI: 10.1007/s40011-015-0623-9
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Inhibitory Effect of Spirulina platensis Extracts on Bacteria of Clinical Significance

Abstract: Spirulina platensis is one of the most potential microalgae explored for antibacterial, antiviral and anticancerous properties. However, its antibiofilm potential has not been studied. Biofilms are of significant interest as they confer resistance towards antimicrobials and host immunity both in diverse group of bacteria. Exploring Spirulina towards the biofilm would give an easy way of treatment against bacterial pathogens. In this milieu, the antibiofilm potentials of organic extracts prepared from S. platen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…These results confirm those from other studies, in which the highest antimicrobial activity of seaweed extracts is found against Gram positive bacteria [ 43 , 57 ]. A. platensis has been studied as a valuable source of antimicrobial, antiviral and antioxidant compounds but its activity is variable and dependent on the extractive solvent [ 58 , 59 , 60 ]. This cyanobacterium, commercially known as Spirulina, is used in food formulations or as a food supplement [ 6 , 61 ] and in health products [ 62 , 63 , 64 , 65 ], because of its composition rich in proteins and small peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm those from other studies, in which the highest antimicrobial activity of seaweed extracts is found against Gram positive bacteria [ 43 , 57 ]. A. platensis has been studied as a valuable source of antimicrobial, antiviral and antioxidant compounds but its activity is variable and dependent on the extractive solvent [ 58 , 59 , 60 ]. This cyanobacterium, commercially known as Spirulina, is used in food formulations or as a food supplement [ 6 , 61 ] and in health products [ 62 , 63 , 64 , 65 ], because of its composition rich in proteins and small peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Marangoni et al [11] recently investigated the in vitro antifungal activity of a water-extract of S. platensis against 11 strains of C. albicans and reported minimal inhibitory concentrations (MIC50) ranging from 0.125 to 0.5 mg/mL. Lewis Oscar et al [12] recently investigated the anti-biofilm effect of S. platensis methanol extract against numerous bacteria of clinical importance, including S. aureus and Escherichia coli and reported promising results. To our knowledge, no data is available regarding the anti-biofilm interest of S. platensis against C. albicans or S. platensis lipid extract as anti-adhesion agent.…”
Section: Introductionmentioning
confidence: 99%
“…LewisOscar et al [343] demonstrated in vitro study of AgNPs synthesized by Spirulina platensis tested against biofilm formation of P. aeruginosa. The authors reported that 100 µg/mL showed the maximum inhibition, 85.63% of biofilm formation and can be a potential coating medical device such as urinary catheter.…”
Section: Agnps For Cathetersmentioning
confidence: 99%